Room-Temperature Bonding of Lithium Niobate on Single Crystal Diamond Wafer - Chen, D (Elsevier Ltd, 2025)
Lithium niobate (LiNbO3) is a novel inorganic material, widely applicated in optical waveguides, mobile, piezoelectric sensors and optical modulators. Whereas, the properties of LiNbO3 will be degraded dramatically at high-power due to its low thermal conductivity. This paper focuses on the room temperature direct bonding of LiNbO3 to a single crystal diamond (SCD) wafer using a nano-adhesive Mo/Au interlayers. The bonding quality was evaluated by scanning acoustic microscopy, transmission electron microscopy, and tensile testing. The results showed a void-free bonded interface at atomic level, with a tensile strength of approximately 18 MPa. This method could enhance the high-power applications of LiNbO3 devices. © 2024